Vavřička v. Czech (Eur. Ct. H.R.). (December 2022) - Toebes, Brigit
Abstract : On April 8, 2021, the Grand Chamber of European Court of Human Rights delivered an eagerly awaited judgment in the case of Vavřička and Others v. The Czech Republic . It addressed the question of mandatory vaccination in the light of the right to respect for private life under Article 8 of the European Convention on Human Rights (ECHR).